The State of Household Level Financial Literacy and its Determinants : Evidence from Cachar District of Rural Assam - Roy, Manash; Nath, Manna (Arthshastra Indian Journal of Economics & Research, 2025)
Purpose : The paper aimed to measure the status of household-level financial literacy and to explore its determinants in the Cachar district of rural Assam. Methodology : The study was exploratory in nature and collected primary data from 482 households using a multi-stage random sampling method. A composite index was developed to assess financial literacy, and a logistic regression model for a bounded dependent variable was used to explore its determinants. Findings : The study found a low level of financial literacy in the study area. The results of logistic regression analysis indicated that the mean education level of households; asset holdings; accessibility to the newspaper, television, and smartphone; membership in a self-help group; self-employment in the non-agriculture sector; and regular employment were all positively and significantly associated with financial literacy. In contrast, casual employment in the non-agriculture sector and living in a joint family system were negatively and significantly associated with financial literacy. Additionally, Hindu households and those belonging to the general category were found to be financially literate compared to Muslim households and the other marginalized communities in the study area. Practical Implications : Efforts should be undertaken by the government and other concerned organizations to raise households’ level of education, economic status, technological aptitude, and accessibility to mass media for speeding up their level of financial literacy. The creation of a sufficient amount of self-employment and regular employment opportunities could play a vital role in this regard. Furthermore, the establishment of a sufficient number of financial literacy centers should be prioritized to develop sound financial skills among adults and empower them financially. Originality : The present study contributed to the existing literature by conceptualizing household-level financial literacy and developing a corresponding measurement tool. The uniqueness of the study also lay in the fact that it covered the adult members of a household instead of concentrating on the head of the household only.